Flipping the Page: Engaging Elementary Literacy with Interactive Storybooks - Ana, I Ketut Trika Adi; Indriani, Made Sri (English Education Department at FKIP Nommensen University, 2025)
Literacy skills still become a serious challenge for elementary school students in Indonesia. Thus, this research aimed to develop interactive storybooks to support literacy activities at elementary schools. This study can be classified as a research and development study following the Successive Approximation Model. Study data were collected from teachers and students at one of the elementary schools in Bali through interviews, documentation, expert judgment, and questionnaires. Data were analyzed qualitatively and quantitatively. Interview and documentation results underwent qualitative analysis using interactive data analysis models. Expert judgment results were analyzed using the inter-rater agreement model, while questionnaire results were analyzed descriptively and categorized using intervals derived from theoretical ideal reference assessments. The findings revealed a strong preference among students for flipbooks with vibrant illustrations, animal characters, smartphone compatibility, and interactive quizzes. The expert judgment further confirmed the suitability of the content for children and its ability to improve students' understanding of narratives. Besides, students’ feedback indicated high acceptance and enthusiasm for the developed flipbooks. However, it is essential to note that the limitation of the study lies in the evaluation regarding the impact of flipbooks on students' literacy skills, which was not conducted. Therefore, it is crucial to conduct a further study utilizing experimental methodology to validate their effectiveness in improving elementary school student’s literacy.